STUDI KOMPARASI HASIL BELAJAR SISWA ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DENGAN TIPE TSTS PADA MATERI INTERAKSI MAKHLUK HIDUP DENGAN LINGKUNGAN KELAS VII DI SMP NEGERI 11 BATAM - Fenny Agustina; Rahmi Sikumbang; Susanto S (Universitas Riau Kepulauan, 2014)
This observational population is student braze VII SMP Negeri 11 Batam school years 2013 / 2014 consists 12 classes. By use of tech simple random is sampling utilized three classes as sample. Class is with model TGT'S learning brazes VII 2 , Class is with model TSTS'S learning brazes VII 4 , and control class by use of discourse learning model which is class VII 12 . Acquired observational data by use of instrument essays to usufruct studying as essays executed double helix objektif after learning process is finished. analisis's stipubting quiz did by normality quiz and homogeneity quiz. Normality quiz by use of quiz chi square. Of that count result data gets normal distribution. Homogeneity quiz usufructs to study utilizes quiz Barlett , gotten big appreciative or f computing = 571,600 and f table = 1,98 on signifikan's level α = 0,05 since f computing F table therefore samples drd variant be homogeneous. Drawned out into hypothesis quiz by use of quiz analisis variance (anova). Of hypothesis result is gotten f computing = 3892,485 and that result is greater of f table = 3,07 with signifikan's level α = 0,05. So acquired hypothesis answer is refuse H0 at a swoop accepts Ha. So concluded that deep observational it exists komparasi result studies student among model kooperatif's learning type TGT with type TSTS on living thing interaction material with environmentally brazes VII at SMP Country 11 Batam T.A. 2013 / 2014